Education as a Сategory of Private Law - E. V. Kobchikova; T. G. Makarov (Теоретическая и прикладная юриспруденция)
In the present work the category “education” is considered as a category of private law. The authors established the relationship of private law with educational legal relations, revealed that the peculiarity of educational legal relations is the combination of public and private principles in them, and it is also noted that education is an interdisciplinary field. Despite the predominantly public law (administrative) nature of educational legal relations, they also have a private law component, which was the object of this study. The article analyzes private legal relations in the field of education, explores the concept of educational services, describes the features of an educational agreement, shows the place of this agreement among other agreements on the provision of services. At the same time, the authors note that the educational contract belongs to the number of contracts for the provision of actual services, which determines its legal nature.